Identification of Quality Improvement Projects from AUA White Papers. Issue 2 (12th March 2020) - Gretzer, Matthew; Greene, Kirsten; Chung, Benjamin; Kobashi, Kathleen
Abstract: Introduction: Health care professionals often lack training in quality improvement methods, which makes it challenging to participate in improvement efforts. Methods: Following a review of the recently published AUA (American Urological Association) white papers on "Optimizing Outcomes in Urologic Surgery" a detailed list of potential quality improvement projects was created as our AUA Leadership Program project. Results: In this article we familiarize the reader with basic tools used in quality improvement project development and the components of quality initiative planning required for implementation of a sample of the identified projects in clinical practice. The projects identified are derived from the areas highlighted in the AUA white papers addressing preoperative, intraoperative and postoperative considerations for quality and safety. Conclusions: We anticipate that this information will be useful for students, residents and practicing urologists to expand their involvement in quality improvement and build multidisciplinary projects based on the work the AUA has already done in this area.